2019
DOI: 10.1096/fj.201901610
|View full text |Cite|
|
Sign up to set email alerts
|

Blockade of lncRNA‐ASLNCS5088–enriched exosome generation in M2 macrophages by GW4869 dampens the effect of M2 macrophages on orchestrating fibroblast activation

Abstract: In hypertrophic scar (HS) formation, the type 2 immune response induces the alternatively activated macrophages (M2), which manipulate fibroblasts to differentiate into myofibroblasts with active biologic functions and proliferation. Myofibroblasts express α‐smooth muscle actin (α‐SMA) and synthesize and produce additional collagen type I and collagen type III, inducing HS formation. However, studies on the mechanism of M2 macrophage modulation are only based on the recognition of profibrotic factors such as T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…It is believed that M2 macrophage-derived exosomes (M2-exos) transfer certain proteins or signals to tumor cells to regulate their migration (10). Specific long non-coding RNAs (lncRNAs) are preferentially packaged into exosomes, and the abundance of exosomal lncRNA correlates with their expression in the original cells (11). The lncRNA plasmacytoma variant translocation 1 (PVT1), located at 8q24.21, is recognized as an oncogene in diverse cancers, whose aberrant expression is proven to relate to cancer development (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that M2 macrophage-derived exosomes (M2-exos) transfer certain proteins or signals to tumor cells to regulate their migration (10). Specific long non-coding RNAs (lncRNAs) are preferentially packaged into exosomes, and the abundance of exosomal lncRNA correlates with their expression in the original cells (11). The lncRNA plasmacytoma variant translocation 1 (PVT1), located at 8q24.21, is recognized as an oncogene in diverse cancers, whose aberrant expression is proven to relate to cancer development (12).…”
Section: Introductionmentioning
confidence: 99%
“…EVs from macrophages exposed to silica also up-regulate α-SMA expression in fibroblasts due to the abundant miR-125a-5p in these EVs 104 . Moreover, EVs from M2-like macrophages are enriched with miR-328 and lncRNA-ASLNCS5088, which subsequently activates TGF-β and profibrotic factors (e.g., α-SMA, Collagen I) in fibroblasts 105 , 106 .…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…2e and 3c-g). Recent studies have revealed that exosomes mediated intracellular communication 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…These molecules include lncRNAs, microRNAs (miRNAs), messenger RNAs (mRNAs), and proteins 27 . Macrophages secret and transmit certain functional proteins and RNAs to affect various kinds of cells, such as fibroblast and epithelial cells 28,29 . Previous research demonstrates that osteoarthritic chondrocytes secret exosome-like vesicles to facilitate the production of IL-1β in macrophages and aggravate OA progression 30 .…”
Section: Introductionmentioning
confidence: 99%